Correction: AlRasheed et al. Aspartames Alter Pharmacokinetics Parameters of Erlotinib and Gefitinib and Elevate Liver Enzymes in Wistar Rats. Pharmaceuticals 2022, 15, 1400 - Hajer AlRasheed; Aliyah Almomen; Haya I. Aljohar; Maria Arafah; Rana Y. Almotawa; Manal A. Alossaimi; Nourah Z. Alzoman (Pharmaceuticals)
In the original publication [...]